Pan and Tilt Camera Object Tracking Using Ziegler-Nichols Method for Control PID - Imron Imron; Bagus Satria; Fajar Ramadhani (Jurnal Ilmu Komputer dan Sistem Informasi (JIKOMSI), 2023)
Cameras are widely used in video surveillance in observing and monitoring various conditions. The purpose are monitored, primarily for surveillance, security, and object tracking. Plant Pan and Tilt is part of changing the rotation of the horizontal and vertical axis of the camera to move to follow the object or as needed. Pan and Tilt movement control is carried out with three types of settings, namely (PID) proportional, integral, and derivative. To work properly, certain parameters, called constants, must be set in each case. Each parameter type has its own strengths and weaknesses. This research uses a technique that can be used for control, the closed-loop Ziegler-Nichols. The method is a heuristic method used in disturbance rejection. The control is carried out using Arduino as the actuator control command and python as the command on the camera with serial communication. The ziegler-nichols method is used as a way to set the PID close-loop. The Plant Pan and Tilt tracks the ball using a camera connected to a computer as a sensor, and a servo connected to an Arduino as an actuator. The results obtained by horizontal rotation get a value proportional 0.24, integral 1.371, and derivative 0.0105. vertical value rotation get proportional 0.21, integral 1.2, and derivative 0.0092.